2000
DOI: 10.2460/javma.2000.217.1678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of limited food consumption on radiographic evidence of osteoarthritis in dogs

Abstract: Prevalence and severity of osteoarthritis in several joints was less in dogs with long-term reduced food intake, compared with control dogs. Food intake is an environmental factor that may have a profound effect on development of osteoarthritis in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
1
15

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 9 publications
(5 reference statements)
5
129
1
15
Order By: Relevance
“…The mean age of the Cairn Terrier was 4.9 years at the second evaluation. The mean interval of 38 months between evaluations should be enough time to allow development of osteoarthritis in dogs initially scored C, D or E. This is supported by Kealy, et al, Smith, et al, and Farrell, et al who all found progression of osteoarthritis with time and Malm, et al found significant increase of pain in dogs suffering from osteoarthritis after 12 months interval examinations most published studies of progression of osteoarthritis in the dogs are based on larger breeds and no publication concerning small breed dogs [7][8][9][10][11]. However, there are a few publications on the outcome of specific orthopaedic treatment gives better results in small breed dogs first of all due to weight control has an indirectly influence on the degenerative joint disease by reducing stresses on the joint [12][13][14].…”
supporting
confidence: 62%
“…The mean age of the Cairn Terrier was 4.9 years at the second evaluation. The mean interval of 38 months between evaluations should be enough time to allow development of osteoarthritis in dogs initially scored C, D or E. This is supported by Kealy, et al, Smith, et al, and Farrell, et al who all found progression of osteoarthritis with time and Malm, et al found significant increase of pain in dogs suffering from osteoarthritis after 12 months interval examinations most published studies of progression of osteoarthritis in the dogs are based on larger breeds and no publication concerning small breed dogs [7][8][9][10][11]. However, there are a few publications on the outcome of specific orthopaedic treatment gives better results in small breed dogs first of all due to weight control has an indirectly influence on the degenerative joint disease by reducing stresses on the joint [12][13][14].…”
supporting
confidence: 62%
“…Son animales de similar envergadura, no habiendo ningún obeso, puesto que son animales de trabajo que realizan ejercicio y tienen una dieta sana y equilibrada. Además, la dieta puede ser el motivo por el que, en caso de que el animal desarrolle en un futuro la CHD, su presentación sea tardía y más leve, tal y como se describe en la bibliografía [41][42][43][44][45] . En cuanto a la predisposición racial, en nuestro estudio no se observan diferencias estadísticamente significativas, algo que…”
Section: Discussionunclassified
“…Previous studies have demonstrated that dogs with CR have reduced shoulder OA, 6-year postdiet intervention, and also show decreased incidence of a combination of shoulder and hip OA (Kealy et al 2000;Runge et al 2008). Additionally, the implementation of CR has been linked to greater joint mobility as well as lower triglycerides in a canine OA model (Kealy et al 2000;Lawler et al 2008). A more detailed analysis of the effects of CR on arthritic bone and cartilage changes, and joint inflammation could provide further insight into the mechanisms by which diet and body weight influence OA development with age.…”
Section: Introductionmentioning
confidence: 98%
“…The reduction of adipose tissue, and thereby its associated inflammation, may decrease the possibility of developing a metabolic syndrome, which is typically characterized by insulin insensitivity, dyslipidemia, and hypertension (Weiss and Fontana 2011). Previous studies have demonstrated that dogs with CR have reduced shoulder OA, 6-year postdiet intervention, and also show decreased incidence of a combination of shoulder and hip OA (Kealy et al 2000;Runge et al 2008). Additionally, the implementation of CR has been linked to greater joint mobility as well as lower triglycerides in a canine OA model (Kealy et al 2000;Lawler et al 2008).…”
Section: Introductionmentioning
confidence: 99%